TRAVELLING BEHAVIOR DURING PANDEMIC SITUATION: STUDY ON EAST JAVA SOCIETY IN INDONESIA - Riesyah Putri Auliyah; Yuli Kartika Dewi; Metta Padmalia (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is to determine the influence of situational factors, risk perceptions and attitudes towards travel behavior during Covid-19. The world of tourism is a very sluggish business due to the Covid-19 virus. Many travel businesses have been hit hard enough and are trying to survive bankruptcy due to the changing situation due to the pandemic. The research method used is quantitative research by conducting a survey of 153 respondents domiciled in East Java, who carried out tourism activities in the last 1 year. East Java is one of the groups of people which was like to travel domestically. The data collection technique uses a questionnaire with a Likert scale. This study used multiple regression analysis as an analytical tool to test hypotheses. The data from the questionnaire results were analyzed to test factors and test variables using SPSS 24. The results of this study show that situational factors, risk perceptions and attitudes have a significant positive effect on travel behavior during the pandemic.